EVALUASI KEBERHASILAN KURIKULUM PERGURUAN TINGGI MENGACU KKNI MENGGUNAKAN SISTEM PAKAR - harkam tujantri; Titis Wulandari (LPPM Universitas Muhammadiyah Muara Bungo, 2022)
Based on the Mandate of Law Number 12 of 2012 Article 35 paragraph 2 concerning Higher Education, Regulation of the Ministry of Research, Technology and Higher Education of the Republic of Indonesia Number 44 of 2015 and Amendment to the Indonesian Minister of Research, Technology and Higher Education Number 50 of 2018 concerning National Standards for Higher Education. Curriculum development must refer to the National Higher Education Standards. This development includes aspects of intellectual intelligence, noble character and skills that refer to the Indonesian National Qualifications Framework (KKNI) contained in Government Regulation no. 08 of 2012 and the Law on Higher Education No 12 of 2012 regarding the undergraduate curriculum based on the learning outcomes of the graduate profile. The aim of this development is to achieve quality graduates. For this reason, an expert system is needed in testing the success of the Higher Education curriculum. This study aims to evaluate the success in implementing the curriculum referring to the KKNI appropriately in accordance with learning outcomes (CPL) using an expert system. The expert system created applies the web-based Forward Chaining method with PHP programming. The data processed in this study is the Higher Education Curriculum data referring to the KKNI in the Elementary School Teacher Education Study Program (PGSD) at the Muara Bungo Muhammadiyah Teacher Training and Education College. The results of this study can test the accuracy of the curriculum application referring to the KKNI appropriately, so that it can be used as a recommendation in curriculum preparation by study programs.